Therapeutic potential of Giloe Tinospora cordifolia The Magical Herb of Ayurveda - Bhattacharyya, Chandrayee (International Journal of Pharmaceutical & Biological Archive, 2013)
Therapeutic potential of Giloe Tinospora cordifolia The Magical Herb of Ayurveda